O kaflach z Modliszewic czyli o piecach elity czasów wazowskich - Kajzer, Leszek (Acta Universitatis Lodziensis. Folia Archaeologica, 2010)
The contents of the present paper are considerations concerning specicity of tiles and image (and possibilities of reconstruction) of stoves coming from the 1st half of the 17th century. The author begins with general observations using views of Maria Dąbrowska, and then comes to, published by the same author, stove of so-called Vasa castle in Warsaw. Next, he concentrates on discussing a stove from a manor-house in Modliszewice near Końskie. This stove in white-navy blue colouring, was built at suggestion of Jan Lipski (†1641)in the 30’s of the 17th century. Subsequently, the author discusses other similar stoves from the 1st half of the 17th century, relics of which or only collections of tiles were found during archaeological excavations of castles and other residences in: Nowe Miasto on Warta, Lubawa, Ujazd, Pińczów and Brudzew near Turek. Most of these stoves were built as a result of foundation actions of narrowly understood social elite of the Vasa times, concretely late phases of the reign of Sigismund III (†1632) and the rule of Vladislav IV (1632-1648). The author submits a proposition that in the times of the first ruler mostly white – navy blue stoves with green and yellow elements were built, and since the half of the 30’s of the 17th century only stoves with tiles with blue (navy blue) background and white relief. They represent typical of the early Baroque in Poland ornamentation. Probably therefore they should be treated as artifacts created in a circle of widely understood (in respect of time and space) court of Vladislav IV, or defined as “stoves of the Vasa times elite”.